2017
DOI: 10.1111/crj.12694
|View full text |Cite
|
Sign up to set email alerts
|

The impact of pediatric obesity on hospitalized children with lower respiratory tract infections in the United States

Abstract: Pediatric obesity is an independent risk factor for severity and morbidity among pediatric patients with lower respiratory tract infections. These findings suggest the importance of obesity prevention for pediatric populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 23 publications
2
27
1
1
Order By: Relevance
“…Obesity is an economically complicating factor for children hospitalized with respiratory infections and asthma in the United States and Japan, where nationwide studies from 2000 to 2012 revealed that obesity was consistently associated with increased hospitalization costs and prolonged length of hospital stay among children with pneumonia or asthma . In contrast, our results demonstrated that the differences in total costs were insignificant between underweight, normal‐weight, overweight, and obese infants.…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…Obesity is an economically complicating factor for children hospitalized with respiratory infections and asthma in the United States and Japan, where nationwide studies from 2000 to 2012 revealed that obesity was consistently associated with increased hospitalization costs and prolonged length of hospital stay among children with pneumonia or asthma . In contrast, our results demonstrated that the differences in total costs were insignificant between underweight, normal‐weight, overweight, and obese infants.…”
Section: Discussioncontrasting
confidence: 65%
“…Most previous studies have focused on the burden of obesity on respiratory infections, categorizing underweight subjects together with normal‐weight subjects as non‐obese . Therefore, little is known about the effects of underweight status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The prevalence of childhood obesity increased between the period from 1990 to 2007 and then leveled off . Recently, several studies have reported that paediatric obesity was associated with high illness severity for acute and chronic diseases, and the health care costs attributable to obesity were gradually rising …”
Section: Introductionsupporting
confidence: 84%